Long-term evaluation of safety and biological effects of Korean Red Ginseng (Panax Ginseng): a long-term in vivo study - Soo Kyung Park; Sung-Won Kim; Hwi Won Seo; Sun Hee Hyun; Jong-Su Kyung; Soo-Hyun Youn; Seung Ho So; Gyo In; Chae-Kyu Park; Eugene C. Yi; Chang-Kyun Han; Yong Yook Lee (BMC, 2022)
Abstract Background Although Korean Red Ginseng (KRG) is safe, this finding was only evaluated in 3-mo-long studies. Its safety was verified through a 6-mo KRG administration clinical study, but long-term studies beyond 6 mo are insufficient. This study investigated the safety and efficacy of 12-mo KRG administration. Methods In this study, 300 mg/kg of KRG was administered to male and female Sprague Dawley rats for 4, 8, and 12 mo to evaluate its efficacy and safety. Clinical signs, including pathological examination and haematological analyses, were observed. Flow cytometric analyses were utilised to analyse spleen and thymus immune cell counts after 12 mo. Proteomic analysis of the sera was performed using a nanospray-interfaced mass spectrometer with an 11-plex Tandem Mass Tag (TMT) labelling system. Bioinformatic analysis was then performed using Ingenuity Pathway Analysis and PANTHER. Data are available via ProteomeXchange with identifier PXD032036. Results No significant body and organ weight changes were observed, and haematological and serum biochemical analyses did not show clinical significance. The effectiveness of long-term KRG administration was confirmed through increased immune cell distribution and activity. Changes in proteins correlated with viral infection reduction were confirmed through proteomic analysis. Conclusion The results suggested that 12-mo KRG intake is safe, improves immune system activity, and reduces viral infections with no significant changes in toxicological aspects.